Influencer Marketing and Purchasing Decisions: The Mediating Role of E-WOM on TikTok - Viola Meiyandri; Lie Heng (Target : Jurnal Manajemen Bisnis, 2025)
The increasingly fierce competition in the cosmetics industry, driven by the growing use of TikTok as a platform for information and shopping, has created an urgency to understand how digital marketing influences Gen-Z purchasing decisions in the modern marketing era. Influencer marketing is rapidly growing as a key strategy, but its effectiveness remains inconsistent and depends on the platform and audience context. Therefore, this study aims to analyze the influence of influencer marketing on pur- chasing decisions and to examine the role of electronic word of mouth (E-WOM) as a mediating variable among TikTok Shop users in Pontianak City. The study used a quantitative method, administering a questionnaire to 123 Gen-Z female respondents selected through purposive sampling. Data analysis was conducted using SEM-AMOS and the Sobel Test to examine the mediating effect more comprehensively. The results indicate that influencer marketing significantly influences E-WOM and purchasing decisions. Additionally, E-WOM has been shown to influence purchasing decisions strongly. The Sobel Test con- firms that E-WOM partially mediates the relationship between influencer marketing and purchasing decisions. These findings confirm that although influencers can generate initial interest, positive reviews from other consumers are an important factor in converting that interest into confidence and actual purchasing behavior. This study implies that digital marketing strategies should integrate influencer collaboration with E-WOM reinforcement to increase the effectiveness of promotions on TikTok Shop.